2020
DOI: 10.5194/tc-2020-187
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-scale snowdrift-permitting modelling of mountain snowpack

Abstract: Abstract. The interaction of mountain terrain with meteorological processes causes substantial temporal and spatial variability in snow accumulation and ablation. Processes impacted by complex terrain include large-scale orographic enhancement of snowfall, small-scale processes such as gravitational and wind-induced transport of snow, and variability in the radiative balance such as through terrain shadowing. In this study, a multi-scale modeling approach is proposed to simulate the temporal and spatial evolut… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…Relevant drivers of snowpack and glacier evolution that are not yet included comprise internal snowpack energetics and the full energy balance, longwave losses, turbulent heat fluxes, sublimation, and canopy-snow interactions. While the recent literature has shown that the added value of complex, physics-based snow models over more parsimonious alternatives for variables that are relevant to hydrology may sometimes be elusive (Rutter et al, 2009;Magnusson et al, 2015;Zaramella et al, 2019;Girons Lopez et al, 2020;Günther et al, 2019), designing more holistic and physics-based operational models remains a key to achieving the most accurate representation of snow temporal dynamics and spatial patterns, especially at fine resolutions (see, for example, the results in Lafaysse et al, 2017;Vionnet et al, 2021). Strategies to include these processes in future releases of S3M are discussed in Sect.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Relevant drivers of snowpack and glacier evolution that are not yet included comprise internal snowpack energetics and the full energy balance, longwave losses, turbulent heat fluxes, sublimation, and canopy-snow interactions. While the recent literature has shown that the added value of complex, physics-based snow models over more parsimonious alternatives for variables that are relevant to hydrology may sometimes be elusive (Rutter et al, 2009;Magnusson et al, 2015;Zaramella et al, 2019;Girons Lopez et al, 2020;Günther et al, 2019), designing more holistic and physics-based operational models remains a key to achieving the most accurate representation of snow temporal dynamics and spatial patterns, especially at fine resolutions (see, for example, the results in Lafaysse et al, 2017;Vionnet et al, 2021). Strategies to include these processes in future releases of S3M are discussed in Sect.…”
Section: Model Descriptionmentioning
confidence: 99%
“…More sophisticated wind downscaling (e.g. Vionnet et al, 2021;Wagenbrenner et al, 2016) could help improve further modelling at this site and other upland icefield-outlet valley glacier settings.…”
Section: Suitability Of Narr For Model Forcing 655mentioning
confidence: 99%
“…Other types of models like WindNinja (Wagenbrenner et al, 2016;Rios et al, 2018;Hilton and Garg, 2021) and TopoSCALE (Fiddes and Gruber, 2014) are based on physical descriptions of wind-topography interactions and are not bound to the domain of calibration. WindNinja is used frequently for wildfire propagation, but was used recently by Vionnet et al (2021) to model snowdrift. However, given their generic nature, those methods do not benefit from the valuable information of measurements or high-resolution simulations and thus might not perform well in particular terrain under particular conditions.…”
Section: Introductionmentioning
confidence: 99%
“…WindNinja is used frequently for wildfire propagation, but was used recently by Vionnet et al . (2021) to model snowdrift. However, given their generic nature, those methods do not benefit from the valuable information of measurements or high‐resolution simulations and thus might not perform well in particular terrain under particular conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation